Implementasi Manajemen Tenaga Pendidik di Madrasah Tsanawiyah Salafiyah Safi'iyah Tebuireng Jombang - Senang Senang (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2017)
Educator management in terms of planning, recruitment, selection, training, performance, appraisal and compensation is an activity that must be done to gain qualified educators. This esearch is aimed to reveal planning, recruitment, selection, training, performance, appraisal and compensation of educators and described the management process of educators done by MTs Salafiyah Safi'iyah Tebuireng Jombang. This research is qualitative with case study. The results are the first, planning educator mostly has been correlated to the analysis of job recruitment and selection and coaching explicitly. Second, the recruitment and selection activities are not publicly and very limited. Third, coaching has been done represent pattern of systematic planning either in the procedure or the determination of the program, meanwhile the assessment of educator performance has been based on the standard of procedure. Fourth, direct or indirect compensation has been set in the rules and regulations.